Right after the weather [compact disc, unabridged] - Anshaw, Carol, 1946- (Simon & Schuster Audio, 2019)
It's the fall of 2016. Cate, a set designer in her early forties, lives and works in Chicago's theater community. She has stayed too long at the fair and knows it's time to get past her prolonged adolescence and stop taking handouts from her parents. She has a firm plan to get solvent and settled in a serious relationship. She has tentatively started something new even as she's haunted by an old, going-nowhere affair. Her ex-husband, recently booted from his most recent marriage, is currently camped out in Cate's spare bedroom, in thrall to online conspiracy theories, and she's not sure how to help him. Her best friend Neale, a yoga instructor, lives nearby with her son and is Cate's model for what serious adulthood looks like. Only a few blocks away, but in a parallel universe, we find Nathan and Irene-casual sociopaths, drug addicts, and small-time criminals. Their world and Cate's intersect the day she comes into Neale's kitchen to find these strangers assaulting her friend.